Geomorphological influence on groundwater quality and arsenic distribution in parts of Brahmaputra river basin adjoining eastern Himalayas - Verma, S.; Mukherjee, Abhijit (2014)
© 2014, Capital Publishing Company. The present study attempts to understand the controls of geomorphological terrains on groundwater geochemistry and groundwater arsenic (As) distribution in the shallow aquifers of parts of the Brahmaputra floodplains of India. Three different geomorphologic units e. g. older alluvial (OA), younger alluvial (YA) and river channel deposits (RCD) were identified as predominant geomorphic terrains in the study area by coupled remote sensing and field observations. Groundwater compositions in the aquifers of these terrains were dominated by Ca-Na-HCO 3 and Na-Ca-HCO 3 hydrogeochemical facies. At least 60 % groundwater samples of study areahave As = 0. 01 µg/L. The reductive dissolution of (Fe-Mn)OOH is the dominant mechanism of As mobilization in different alluvial terrains and redox transitions play major role for As mobilization in groundwater.